2000
DOI: 10.1046/j.1442-200x.2000.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors affecting psychosomatic symptoms in Japanese schoolchildren

Abstract: Children in the older age reflect the closer bio-psycho-socio interaction compared with their younger counterparts. This may give rise to a high incidence of psychosomatic disorders and school refusal in Japanese children. We emphasize that psychological support by parents in daily life is necessary to reduce psychosomatic symptoms in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 2 publications
2
47
0
3
Order By: Relevance
“…These [17,[31][32][33]. The aim of our study was to examine associations between Swedish parents' activities together with their children, the parents' experiences of time pressure and the children's health.…”
Section: Discussionmentioning
confidence: 99%
“…These [17,[31][32][33]. The aim of our study was to examine associations between Swedish parents' activities together with their children, the parents' experiences of time pressure and the children's health.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of childhood stress and psychosomatic and emotional symptoms (PES) has been increasing in parallel over the last decade, indicating that adverse, stressful circumstances may trigger PES in children [6,9,[12][13][14][15][16][17][18][19][20][21]. Moreover, multiple simultaneous or sequential stressors may increase the risk for psychosomatic or emotional problems in a cumulative or additive way [13,[18][19][20][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest the possibility that psychosomatic symptoms could be prevented by improving lifestyle behaviors. There have been studies focused on individual lifestyle behaviors, such as sleeping hours and bedtimes, and there have also been a number of studies on the relationships between psychosomatic symptoms and life events, social support, and self-efficacy (21,(23)(24)(25)(26)(27)(28)47). Only a few studies, however, have reported on the relationship of overall lifestyles with psychosomatic symptoms among children.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies of the relationships between life events, social support, and psychosomatic symptoms (23)(24)(25)(26)(27)(28). Other studies have investigated the association of lifestyle behaviors with psychosomatic symptoms (29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%